Liquidity Constraints and Demand for Healthcare: Evidence from Danish Welfare Recipients - Frederik Plesner Lyngse (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
Are low-income individuals relying on government transfers liquidity constrained by the end of the month to a degree that they postpone medical treatment? I investigate this question using Danish administrative data comprising the universe of welfare recipients and the filling of all prescription drugs. I find that on transfer income payday, recipients have a 52% increase in the propensity to fill a prescription. By separating prophylaxis drugs used to treat chronic conditions, where the patient can anticipate the need to fill the prescription, e.g. cholesterol-lowering statins, I find an increase of up to 99% increase on payday. Even for drugs used to treat acute conditions, where timely treatment is essential, I find a 22% increase on payday for antibiotics and a 5-8% decrease in the four days preceding payday. Lastly, exploiting the difference in day the doctor write the prescription and the day the patient fill it, I show that liquidity constraints is the key operating mechanism for postponing antibiotic treatment.
Keywords: I12; I13; I14; 330; health behavior; health insurance; health and inequality; prescription drugs; payday